Evaluation Inclusive Education in Higher Education: Development and Implementation of Assessment Indicators - Zadry, Hilma Raimona; Huda, Ashila Nurul; Susanti, Lusi; Fitri, Sri Rahmah (invotek, 2025)
The 1945 Constitution of Indonesia ensures education access for all citizens. Law No. 19 of 2011 ratifies the Convention on the Rights of Persons with Disabilities (CRPD), emphasizing inclusive education. Despite efforts by several universities, including Universitas Andalas, challenges remain. A preliminary survey with five students with disabilities at Universitas Andalas identified barriers such as communication difficulties, limited library resources for the visually impaired, and inadequate public facilities. However, no formal research or evaluation indicators have been developed to assess the university's inclusivity. This study aims to develop self-evaluation indicators for improving inclusive education at Universitas Andalas. Using qualitative and quantitative methods, it examines challenges, formulates evaluation indicators, and assesses implementation. The proposed indicators cover seven aspects: institutional policies, admissions, learning, socio-psychological support, physical accessibility, graduate preparedness, and teaching methods. The evaluation results highlight institutional policies, social support, and learning methods as the strongest aspects, whereas physical accessibility scores the lowest. Universitas Andalas attained a self-evaluation score of 483, categorizing it as "Moderately Inclusive." Key recommendations include improving infrastructure such as accessible dining areas, specialized learning tools, laboratories, and libraries. Additional measures include career training programs, inclusive teaching workshops for faculty, periodic policy updates, and enhanced counseling services. These improvements aim to establish Universitas Andalas as a more disability-friendly institution, ensuring equal opportunities for all students.